Implementation Of Strategies To Increase Competitive Advantage And Company Survival Post Pandemic Covid-19 In The Industrial Revolution 6.0 - Suhardoyo (International Journal of Science, Technology & Management, 2022)
The business strategy plays an important role in the manufacturing industry sector as an effort to increase income and maintain business viability which is very necessary to deal with the problems of the post-covid19 pandemic in the 6.0 revolution era, resulting in a decrease in the company's income level resulting in a weakening of the ability to maintain business viability and competitiveness can be avoided. Many companies go bankrupt and die in business activities because they have not properly implemented their business strategies. PT. DS Global is one of that can survive with unfavorable economic conditions, this company has implemented various strategies, strategies related to human resource management as well as the use of technology and information supported by company resources as a unit that cannot be separated and influence each other in the implementation of its business process activities. Human resource management strategy, strategic uses of information technology, building a customer-focused business, value chain strategy, and strategy to build a knowledge-creating company. The strategy carried out by the company has been able to create conditions to maintain survival and be able to compete in the era of the industrial revolution 6.0 and face the post-covid-19 pandemic resurgence that has hit the world today.